Using the ecosystem services approach to link raptors with human well-being in the Southeast Pampas of Argentina - Gorosabel, Antonella; Bernad, Lucía; Muñoz, Sebastián Darío; Pedrana, Julieta (Springer, 2022)
Understanding the link between biodiversity, ecosystem services and human well-being is necessary to work towards a sustainable use of agroecosystems and the conservation of biodiversity. We aimed to identify the role raptors have in the provision of potential regulating ecosystem services in agroecosystems of the Argentine Pampas. We used the Ecological Niche Factor Analysis to construct habitat suitability maps for each species using presence data and environmental variables. Based on a literature review, we classified raptors into five guilds based on their ecological function and main food preferences (mammal consumer, insect consumer, bird consumer, snail consumer and scavengers). Each guild was associated with a potential ecosystem service based on the detrimental effects of the main prey items. We overlapped all maps to develop ecosystem services hotspot maps. We found that raptors played an important role in rodent and insect control and scavenging mainly in crops and grazing lands, while bird and snail control were mainly done in landscapes composed by high percentages of natural areas. Habitat suitability maps were used to explore the potential impacts of different land managements on raptors and its potential benefits, allowing the coexistence of wildlife with agricultural activities. Hotspot maps highlight the importance of integrating natural areas in rural landscapes, which supported more species that could be translated into more benefits for human-wealth.